The Rejection of Kyai Nahdlatul Ulama to the Anti-Polygamy Bill For The Dutch East Indies Colonial Government (International Journal of Scientific Research and Management (IJSRM), 2022)
This study seeks to convey the Kyai NU’s position on the anti-polygamy Bill, as well as the grounds behind their refusal. In the historical context, a Bill to abolish the practice of polygamy in Indonesian culture has existed since the Dutch East Indies Colonial control, the anti-polygamy Bill is called the Ontwerp Ordonnantie Marriage Boemipoetra. The Dutch East Indies colonial governement distributed the anti-polygamy Bill to all Islamic groups in Indonesia in order to get replies and views from these Islamic associations, which would serve as the foundation for the colonial government to approve or repeal the Bill. A literature-based study was carried out to gather, investigate, and analyze various literatures related to the Kyai NU’s perspectives on the anti-polygamy Bill offered by the Dutch East Indies Colonial Government. The result of study shows that the execution of the anti-polygamy Bill is categorically rejected by Nahdlatul Ulama. This rejection is motivated by both religious and social considerations.